Answer:
see explanation
Explanation:
Given
2x² + 4 = - 5x + 1
To express in standard form subtract - 5x + 1 from both sides
2x² + 5x + 3 = 0 ← in standard form
Consider the factors of the product of the x² term and the constant term which sum to give the coefficient of the x- term
product = 2 + 3 = 6 and sum = + 5
The factors are + 2 and + 3
Use these factors to split the x- term
2x² + 2x + 3x + 3 = 0 ( factor the first/second and third/fourth terms )
2x(x + 1) + 3(x + 1) = 0 ← factor out (x + 1)
(x + 1)(2x + 3) = 0
Equate each factor to zero and solve for x
x + 1 = 0 ⇒ x = - 1
2x + 3 = 0 ⇒ 2x = - 3 ⇒ x = -
![(3)/(2)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/85tww783zdtzzps1k74cyql3cl3s1y42ha.png)